Entrepreneurship in law "ohada" : comparative analysis in the light of the french system-summary - (:unkn) unknown (My University, 2019)
This thesis addresses the problem of the abundance of activities in the informal economy in Africa that escape the control and regulation of the state. The objective is to participate through a legal debate of a continental dimension, to the analysis of the role of the entrepreneur in economic development. In the context of changing business law, it is particularly important to focus on the role of the entrepreneur as an economic actor. We propose a comparative approach in the light of French law to encourage business creation in the states of West Africa. With this in mind the OHADA legislator intervenes with a view to putting in place a simplified regulation allowing individuals to get into the business world, without subjecting themselves to severe constraints of legality. The integration of Entrepreneurship by the bill of revision of the Uniform Act on Company Law and Economic Interest Grouping of January 31, 2014, the Uniform Act on General Commercial Law of December 15, 2010, the Uniform Act relative to the law of cooperative companies of December 15, 2010, constitutes a fundamental lever.New regulations are now issued to professionals who were not governed by commercial law. This major innovation reflects this desire to involve all citizens in economic development. The purpose of the present study is to analyze the advantages and the disadvantages of this ease of management offered by OHADA law entrepreneurship through an overview of the uniform acts concerning the creation of a company. Finally, we discuss the relevance of this approach by comparing it with the very advanced French model of entrepreneurship. Through the importance given to micro credit, the diversification of financing methods, the formal sector, but also and above all to the change of status. The entrepreneur in OHADA law has enormous similarities with the status of auto-entrepreneur resulting from an innovation of French legislation by the law of modernization of August 4, 20
Keywords: African Research